Fed-Batch Cultivations of Rhodospirillum rubrum Under Multiple Nutrient-Limited Growth Conditions on Syngas as a Novel Option to Produce Poly(3-Hydroxybutyrate) (PHB) - Karmann, Stephanie; Panke, Sven; Zinn, Manfred (Frontiers in Bioengineering and Biotechnology, 2019)
Syngas from gasified organic waste materials is a promising feedstock for the biotechnological synthesis of the bioplastic poly([R]-3-hydroxybutyrate) (PHB) with Rhodospirillum rubrum. In a first approach, growth studies were carried out with this strain in gas-tight serum vials. When syngas (40% CO, 40% H2, 10% CO2, 10% N2 v/v) was diluted with N2 to 60%, a 4 times higher biomass production was detected than for samples grown on 100% syngas, thus indicating a growth inhibitory effect. The best performing syngas-mixture was then used for C-, C,N- and C,P-limited fed-batch fermentations in a bioreactor with continuous syngas and acetate supply. It was found that C,P-limited PHB productivity was 5 times higher than for only C-limited growth and reached a maximal PHB content of 30% w/w. Surprisingly, growth and PHB production stopped when N, as a second nutrient, became growth-limiting. Finally, it was concluded that a minimal supply of 0.2 g CO g-1 biomass h-1 has to be guaranteed in order to cover the cellular maintenance energy.